Trade, Firm Selection and Innovation: The Competition Channel. (7th August 2017) - Impullitti, Giammario; Licandro, Omar
Abstract : We study the welfare gains from trade in an economy with heterogeneous firms, variable markups and endogenous growth. Variable markups arise from oligopolistic competition, and cost‐reducing innovation is the engine of long‐run growth. Trade liberalisation stiffens competition by reducing markups, generating tougher firm selection and increasing the aggregate productivity level. Selection increases firms' incentives to innovate, thereby leading to a higher aggregate productivity growth rate. Endogenous productivity growth boosts the selection gains from trade, leading to substantial welfare improvements. A calibrated version of the model shows that growth doubles the welfare gains obtainable in models with static firm‐level productivity.